Comparison of fatigue in fiber-backed PVDF and PFA fluoropolymer linings. (April 2019) - Gilmore, Benjamin; Luscher, Zachary; Roberts, Kyle; Fisher, George; Sparks, Taylor D.
Abstract: In this work comparative mechanical fatigue experiments were performed in order to quantify the mechanical stress delamination rates for both PVDF and PFA lining materials. Evidence was found for a Paris Law behavior when samples are cycled in blister test configurations. PFA liners exhibited crack growth constants C = 0.0486 c m / c y c l e and n = 0.9 while PVDF liners exhibited crack growth constants C = 0.0999 c m / c y c l e and n = 0.8 . Linear crack growth rates were observed which ranged from 0.042 ( ( a / a 0 ) / c y c l e ) at 3.10 bar up to 1.47 ( ( a / a 0 ) / c y c l e ) at 4.48 bar for PVDF and 0.024 ( ( a / a 0 ) / c y c l e ) at 2.59 bar up to 0.262 ( ( a / a 0 ) / c y c l e ) at 3.79 bar for PFA. PFA liners were found to fail at 5.52 bar while PVDF liners failed more violently at 6.21 bar. Overall fatigue ratings of the PVDF vs PFA linings should balance the faster delamination rates of PVDF liners vs the lower strength of PFA liners. It is unlikely that vessels with PVDF or PFA liners under fatigue failure due to vacuum-induced mechanical stresses since much larger stresses were required to cause low cycle fatigue failure. Instead, sample delamination is likely due to thermal stresses arising from a mismatch in thermal expansion between liner, fiber backing, epoxy, and metal substrate. Highlights: First of its kind Paris Law-based fatigue analysis of fluoropolymer lining delamination via optical crack growth monitoring. PVDF and PFA crack growth rate analysis and maximum blister pressure measurement. Comparative analysis of delamination of industry standard linings under blister testing conditions.